The Influence of Work-life Balance and Workload on Employee Performance through Physical Well-being - Ely Aeni Dieka Prahesti; Rr. Hawik Ervina Indiworo; Ika Indriasari (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2026)
This research was conducted to examine the effect of work-life balance, workload, and physical well-being on employee performance at PT Widodo Karya Sejahtera, with physical well-being acting as an intervening variable. The study employed a quantitative research design using a survey method by distributing questionnaires to production employees. The collected data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) technique with the assistance of SmartPLS software. The findings indicate that work-life balance and physical well-being have a positive and significant influence on employee performance. Meanwhile, workload does not show a significant effect on employee performance. Furthermore, the results also demonstrate that physical well-being significantly mediates the relationship between work-life balance and workload with employee performance.